Kader Posyandu Sebagai Aset Pertahanan Negara dalam Penanggulangan Ancaman Stunting - Muhammad Novrianto; Ari Pitoyo Sumarno; Edy Saptono (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Stunting in Indonesia presently constitutes a strategic threat that may undermine the nation's people resources and national resilience. Posyandu cadres operate at the forefront and fulfill a vital function. They frequently encounter structural impediments that hinder their proper functioning. This study seeks to examine the function of Posyandu cadres through the lens of a national defense paradigm, aiming to clarify conceptual discrepancies in the current literature. The research employed a systematic literature review to evaluate and integrate results from many pertinent scholarly journals. The investigation verified that the acknowledged function of cadres is ineffective due to ongoing structural problems, including capacity deficiencies and insufficient incentives. Significantly, it was discovered that there was no discourse connecting the role of cadres to the notion of national defense, highlighting a deficiency in coherence within academic research. This paper presents a novel conceptual framework characterizing cadres as "human security agents." This indicates a transition in policy focus from social programs to strategic expenditures in non-military security infrastructure.